Semantic Echoes of a Name: Malinche in the Intercultural Dimension of Laura Esquivel`s Novel - Шестопал, Ольга (Київський національний університет імені Тараса Шевченка, 2026)
Background. This article examines Laura Esquivel’s novel Malinche (2006) as a literary reconfiguration of the legendary figure of Malinche – Hernán Cortés’s translator and intermediary – within feminist and decolonial frameworks. The topic remains relevant due to Malinche’s profoundly ambivalent status in Mexican cultural memory: she has been persistently reduced to an emblem of betrayal (most notably through Octavio Paz’s "La Chingada"), while alternative readings foreground her as a mediator of languages, cultures, and historical ruptures. The aim of the study is to demonstrate how the heroine’s shifting names operate as a semantic and ideological mechanism through which the novel stages power relations, trauma, and resistance, and how the narrative restores the colonized woman’s right to self-naming as a form of agency. Methods. The research employs an interpretive textual analysis, combined with postcolonial and decolonial approaches (particularly W.  Mignolo’s and T. Todorov’s conceptualizations of coloniality, translation, and the "other"). Principles of feminist criticism are applied to trace the transformation of the patriarchal myth of the "traitor" into a narrative that restores a voice to a colonized woman. Results. The analysis shows that the three key names – Malinalli, Doña Marina, and Malinche – generate a polyphonic field of meanings and correspond to distinct regimes of symbolic control. Malinalli evokes autochthonous spirituality, embodied memory, and ancestral continuity; Marina signifies colonial appropriation, institutional recognition, and linguistic power; Malinche reveals the paradox of historical remembrance, shifting from the conquistador’s nickname to a stigma imposed on the woman. The variability of naming functions as a decolonial strategy: reclaiming the original name, re-establishing genealogical ties, and articulating collective trauma as something that can be narrated rather than silenced. Conclusions. Esquivel’s novel dismantles the reductive stereotype of Malinche as a "traitor" and reframes her as a carrier of intercultural memory and a foundational figure in the emergence of a new Mexican subjectivity. The semantic "echoes" of Malinche’s name thus become a metaphor of restoration: memory contests violence, language becomes a site of ethical reparation, and self-naming opens a space for dialogue, historical accountability, and hope.

Вступ. У статті проаналізовано роман Лаури Есківель "Малінче" (2006) як художню модель сучасного переосмислення легендарної постаті Малінче – перекладачки й посередниці Ернана Кортеса – у координатах феміністичного та деколоніального мислення. Актуальність дослідження зумовлена контроверсійністю образу Малінче в мексиканській культурній пам’яті: від символу зради ("La Chingada в інтерпретації" Октавіо Паса) до фігури, що уособлює складні механізми міжкультурного обміну, мовної медіації та народження нової ідентичності. Мета – простежити, як варіативність імен героїні функціонує як семіотичний інструмент репрезентації влади, травми та опору, і яким чином наратив "повертає" жінці право на власне ім’я як право на голос. Методи. Дослідження спирається на інтерпретативний аналіз тексту в поєднанні з постколоніальним і деколоніальним підходами (зокрема, концепції В. Міньйоло та Ц. Тодорова), що дають змогу розглядати ім’я як маркер культурної належності й символічного привласнення. Залучено принципи феміністичної критики для висвітлення трансформації патріархального міфу про "зрадницю" у наратив, який артикулює досвід колонізованої жінки. Результати. Показано, що три імені героїні – Маліналлі, донья Марина та Малінче – формують поліфонічний простір значень і віддзеркалюють різні режими влади. Маліналлі актуалізує автохтонну духовність, тілесну пам’ять і зв’язок із предками, Марина репрезентує колоніальне привласнення й мовну владу, а Малінче унаочнює парадокс історичної пам’яті, трансформуючись із прізвиська конкістадора на стигму для жінки. Виявлено, що варіативність імен слугує інструментом деколонізації: повернення героїні первинного імені, реконструкцію родової пам’яті та проговорення колективної травми. Висновки. Роман Л. Есківель деконструює стереотипний образ Малінче як "зрадниці" й пропонує її як носійку міжкультурної пам’яті та символ народження нового соціокультурного суб’єкта. Семантичні "відлуння" імені в тексті виконують роль метафори відновлення цілісності: слово стає простором опору, пам’ять – механізмом зцілення, а право на власне ім’я – засадою етичного діалогу.
Семантичні відлуння імені: Малінче в міжкультурному вимірі роману Лаури Есківель
Keywords: Malinche; decolonization; linguistic power; names and identity; intercultural dialogue; cultural memory; Mexican literature; Малінче; деколонізація; мовна влада; імена та ідентичність; міжкультурний діалог; культурна пам’ять; мексиканська література